Design and development of robotic arm car for lightweight object handling - Mohd Hussin, Amirul Hussaini; Tengku Mohd Faiz, Tengku Muhammad Adam; Mohd Suhaimi, Muhammad Aqim; Mohd Nizam, Harries Eidman; Roslan, Liyana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Traditional robotic arm systems provide challenges for application in educational environments since they frequently remain stationary with limited workspace and need sophisticated technical expertise to handle. This project addresses these challenges through the design and development of an integrated robotic arm car specifically designed to pick and move lightweight objects in indoor conditions. The goal is to build a robotic arm car with a working grabber that ensure structural stability, controlled movement, and simplicity of usage. The methodology involved a systematic design approach using SolidWorks for 3D modelling and stress analysis, followed by fabrication using laser-cut acrylic and 3D-printed PLA components. The robotic system integrates a grabber and 3-DOF arm on a four-wheeled platform with a Bluetooth connectivity and a custom MIT App Inventor interface as controller. The results from stress analysis verified the structural integrity of critical components, which demonstrates minimal deformation for all components. The successful implementation validates that the integrated design approach successfully creates a prototype of robotic arm car capable of executing basic object manipulation tasks while offering useful hands-on experience with robotic fundamentals.